The ectopic expression of Arabidopsis glucosyltransferase UGT74D1 affects leaf positioning through modulating indole-3-acetic acid homeostasis - Shanghui Jin (Nature Portfolio, 2021)
Abstract Leaf angle is an important agronomic trait affecting photosynthesis efficiency and crop yield. Although the mechanisms involved in the leaf angle control are intensively studied in monocots, factors contribute to the leaf angle in dicots are largely unknown. In this article, we explored the physiological roles of an Arabidopsis glucosyltransferase, UGT74D1, which have been proved to be indole-3-acetic acid (IAA) glucosyltransferase in vitro. We found that UGT74D1 possessed the enzymatic activity toward IAA glucosylation in vivo and its expression was induced by auxins. The ectopically expressed UGT74D1 obviously reduced the leaf angle with an altered IAA level, auxin distribution and cell size in leaf tissues. The expression of several key genes involved in the leaf shaping and leaf positioning, including PHYTOCHROME KINASE SUBSTRATE (PKS) genes and TEOSINTE BRANCHED1, CYCLOIDEA, and PCF (TCP) genes, were dramatically changed by ectopic expression of UGT74D1. In addition, clear transcription changes of YUCCA genes and other auxin related genes can be observed in overexpression lines. Taken together, our data indicate that glucosyltransferase UGT74D1 could affect leaf positioning through modulating auxin homeostasis and regulating transcription of PKS and TCP genes, suggesting a potential new role of UGT74D1 in regulation of leaf angle in dicot Arabidopsis.